The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1038/sj.ejcn.1601165
|View full text |Cite
|
Sign up to set email alerts
|

Social position and nutrition: a gradient relationship in Canada and the USA

Abstract: Obejctive: To study the existence of a graded relationship between the nutrient content of the diet and some measures of social position. Design and setting: The graded relationship hypothesis was veri®ed by secondary analysis performed on two different nutrition surveys: the Quebec Nutrition Survey (QNS) and the NHANES III, both based on a single 24 h recall. The data of these surveys were collected on a representative sample of two different populations, the ®rst (n 2103) in the province of Quebec (Canada) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
31
1
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 16 publications
11
31
1
4
Order By: Relevance
“…In order to explore the role of diet in socio-economic differentials in health and disease, relationships between socio-economic status (SES) and different aspects of the diet have been examined in several different countries (Smith and Baghurst, 1992;Irala-Estevez et al, 2000;Dubois and Girard, 2001;Groth et al, 2001;Giskes et al, 2002). Associations between SES and diet have also been examined along with various other factors (e.g., family status) in order to gain a better understanding of food consumption patterns in relation to dietary recommendations (Roos et al, 1998;Perez, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to explore the role of diet in socio-economic differentials in health and disease, relationships between socio-economic status (SES) and different aspects of the diet have been examined in several different countries (Smith and Baghurst, 1992;Irala-Estevez et al, 2000;Dubois and Girard, 2001;Groth et al, 2001;Giskes et al, 2002). Associations between SES and diet have also been examined along with various other factors (e.g., family status) in order to gain a better understanding of food consumption patterns in relation to dietary recommendations (Roos et al, 1998;Perez, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Associations between SES and diet have also been examined along with various other factors (e.g., family status) in order to gain a better understanding of food consumption patterns in relation to dietary recommendations (Roos et al, 1998;Perez, 2002). The measures of SES employed in these studies vary, where a single variable, such as income, education, occupation or a composite measure based on all three, is used as an indicator of SES (Roos et al, 1998;Irala-Estevez et al, 2000;Dubois and Girard, 2001;Giskes et al, 2002), or two or three variables (e.g., income and education) are included together in one model (Smith and Baghurst, 1992;Groth et al, 2001;Perez, 2002). A number of studies conducted in different countries have shown income and education to have similar effects on food consumption, where higher income and higher education are associated with greater consumption of vegetables and fruit (Billson et al, 1999;Nayga et al, 1999;Irala-Estevez et al, 2000;Groth et al, 2001;Giskes et al, 2002;Perez, 2002), and with diets more in accord with dietary guidelines (Roos et al, 1998;Mancino et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which socioeconomic disadvantage leads to an unhealthy nutrient intake have frequently been discussed (4,8). Food choice and nutrition security are influenced by individual knowledge and training, food price and diet cost, food access, and the food environment, including neighborhood context, cultural issues, and other aspects (4,8).…”
Section: Discussionmentioning
confidence: 99%
“…People of a lower socioeconomic status in terms of education, income, occupational status, etc. have been found to have a poor quality diet (4)(5)(6)(7). An unhealthy dietary intake pattern results in increased risk factors particularly for cardiovascular disease, including obesity, diabetes, and dyslipidemia (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Les féculents raffinés et les pommes de terre sont consommés en plus grande quantité alors que les aliments recommandés pour la santé, tels que les fruits et légumes, le pain complet, les viandes maigres, les poissons et crustacés, sont sous-consommés [39][40][41][42][43] dans ces populations. Ceci s'accompagne d'un très net gradient social des apports en fibres et en micronutriments essentiels, et les différences sont plus marquées pour les nutriments trouvés en abondance dans les fruits et les légumes, tels que la vitamine C, le b-carotène, les folates [32,44,45]. En revanche, les apports en macronutriments, les lipides notamment, sont peu affectés par le SSE des individus (revue de la littérature internationale in [37]).…”
Section: Facteurs Explicatifs Directsunclassified